Liver regeneration after extensive hepatectomy in rats: effect of preoperative chemotherapy with intravenous 5-fluorouracil - Anghinoni,Marciano (2022)
ABSTRACT Purpose: To evaluate the effect of preoperative intravenous chemotherapy with 5-fluorouracil on liver regeneration in an experimental model of major hepatectomy in rats. Methods: Wistar rats were divided into two groups of 20 animals each and submitted to 70% hepatectomy 24 h after intravenous injection of 5-fluorouracil 20 mg/kg (fluorouracil group, FG) or 0.9% saline (control group, CG). After hepatectomy, each group was subdivided into two subgroups of 10 animals each according to the day of sacrifice (24 h or 7 days). Liver weight during regeneration, liver regeneration rate using Kwon formula, and the immunohistochemical markers proliferating cell nuclear antigen (PCNA) and Ki-67 were used to assess liver regeneration. Results: At early phase (24 h after hepatectomy) it was demonstrated the negative effect of 5-fluorouracil on liver regeneration when assessed by Kwon formula (p < 0.0001), PCNA analysis (p = 0.02). With regeneration process complete (7 days), it was possible to demonstrate the sustained impairment of chemotherapy with 5-fluorouracil on hepatocytes regeneration phenomenon when measured by Kwon formula (p = 0.009), PCNA analysis (p = 0.0001) and Ki-67 analysis (0.001). Conclusions: Preoperative chemotherapy with intravenous 5-fluorouracil negatively affected the mechanisms of liver regeneration after major hepatectomy in rats.